The effect of trehalose, sucrose and maltodextrin addition on physicochemical and sensory aspects of freeze - dried strawberry puree - Galmarini, Mara Virginia (2008)
Fil: Galmarini, Mara V. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina